Pesantren Management During The New Normal Era In Indonesia - Muhammad Roihan (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This study aims to carry out the following objectives, (1) evaluate the post-new normal Islamic Boarding School Management in Indonesia, (2) analyze the comparative patterns modern and traditional pesantren management, and (3) determine the new normal era implications for the Islamic institutional management. The Systematic Literature Review method was used to obtain data on the management of modern and traditional pesantren in the new normal era. This included the identification, search for, and analysis of relevant literature. The meta-synthesis and comparisons related to leadership, learning, and the use of digital technology were also conducted. The results showed that pesantren management had been progressive since the Covid-19 pandemic, as observed from the ability of pesantren to adapt during a crisis. The ability to follow trends in management development was also emphasized during the new normal era. However, no significant difference was found between modern and traditional pesantren in managing digital technology, social media, and the internet.